Screening of wheat (Triticum aestivum) variesties tolerant to manganese- deficency stress - BANSAL, R L; NAYYAR, V K (The Indian Journal of Agricultural Sciences, 2013)
Manganese deficiency is a problem in bread wheat (Triticum aestivum L. emend. Fiori & Paol.) production when grown on highly permeable sandy soils cropped with rice (Oryza sativa L.) for 5 or more years. The variation in the ability of wheat varieties to maintain yield on soils with limited Mn availability was investigated. A field experiment was conducted during winter season (rabi) 1995-96 to study tbe tolerance of6 varieties of wheat to manganese stress in a Mn-deficient field containing 2.2 mg DTPA-Mn/kg soil. The treanments included control and 3 foliar sprays of 0.5% manganese sulphate solution. All the varieties responded to foliar application of Mn and tbe increase in grain yield varied from 0.30 to 0.85 tonnes/ha. The macaroni (Triticum durum Desf.) varieties of wheat responded more to Mn (26.4-34.9%) than the Triticum aestivum varieties (7.9-23.0%). Based on tbe increase (%) in grain yield on foliar application of Mn, the varieties were grouped least tolerant (,PBW 34’ and ’PDW 215’), moderately tolerant (,PBW 226’ and ’PBW 343’) and tolerant (,WH 542’ and ’HD 2329’). The grain yield was significantly related with both Mn concentration in flag-leaf (r = 0.80*) and Mn uptake (r = 0.92**).